The Influence of Trust and Ease of Using Paylater on Impluse Buying in Users E-Commerce - Budiarti, Sari; Hardini, Resti; Sudirdja, Putri Fitrah; Annisa, Resi; Hasannuddin, M. Fuad (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
The purpose of this study is to explore the influence of trust and ease of using Paylater on impulse buying tendencies of e-commerce users. This study uses quantitative methods based on a questionnaire obtained from 100 respondents using a Likert scale. This research data was calculated using SPSS through validity & reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, partial t test, simultaneous f test, & coefficient of determination test. The results of this study show that the ease of use of Paylater has a significant positive effect on impluse buying, while trust in Paylater is not proven to have a significant effect on impluse buying. However, the finding of no significant effect of trust in the use of Paylater on impluse buying contradictsprevious research (Verhagen et al, 2011). This difference may be due to different research contexts or other factors that influence consumer trust in Paylater. The conclusion of this study is that the findings of this study add new insights in studying what factors influence impulse buying in the context of e-commerce, especially related to the use of Paylater.